Antimicrobial Resistance and CRISPR Typing Among Salmonella Isolates From Poultry Farms in China - Li, Cui; Wang, Yulong; Gao, Yufeng; Li, Chao; Ma, Boheng; Wang, Hongning (Frontiers in Microbiology, 2021)
Although knowledge of the clustered regularly interspaced short palindromic repeat (CRISPR)-Cas system has been applied in many research areas, comprehensive studies of this system in Salmonella, particularly in analysis of antibiotic resistance, have not been reported. In this work, 75 Salmonella isolates obtained from broilers or broilers products were characterized to determine their antimicrobial susceptibilities, antibiotic resistance gene profiles, and CRISPR array diversities, and genotyping were explored. In total, 80.00% (60/75) of the strains were multidrug resistant, and the main pattern observed in the isolates was CN-AZM-AMP-AMC-CAZ-CIP-ATM-TE-SXT-FOS-C. The resistance genes of streptomycin (aadA), phenicol (floR-like and catB3-like), β-lactams (blaTEM, blaOXA, and blaCTX), tetracycline (tet(A)-like), and sulfonamides (sul1 and sul2) appeared at higher frequencies among the corresponding resistant isolates. Subsequently, we analyzed the CRISPR arrays and found 517 unique spacer sequences and 31 unique direct repeat sequences. Based on the CRISPR spacer sequences, we developed a novel typing method, CRISPR locus three spacer sequences typing (CLTSST), to help identify sources of Salmonella outbreaks especially correlated with epidemiological data. Compared with multi-locus sequence typing (MLST), conventional CRISPR typing (CCT), and CRISPR locus spacer pair typing (CLSPT), discrimination using CLTSST was weaker than that using CCT but stronger than that using MLST and CLSPT. In addition, we also found that there were no correlations between CRISPR loci and antibiotics but had certain correlations between CRISPR loci and antibiotic resistance genes in Salmonella isolates.